Membangun Kesadaran Bersama Melalui Seminar Pencegahan Pelecehan Seksual di SMP Nusa Alam - Wafasari, Wafasari; Prily Wiske Widiya Putri; Leza Puastri Putri (Pendidikan Matematika, FKIP Universitas Mataram, 2024)
Sexual harassment is any form of harassing or degrading behaviour related to sexual urges, harming or making uncomfortable a person who is subjected to such behaviour, or any behaviour that forces a person to engage in sexual intercourse or become an object of unwanted sexual attention, data from the Ministry of Women's Empowerment and Child Protection issued data on the number of cases of violence in 2023 reaching 25,342, and recorded acts of sexual violence that occurred in Mataram City throughout 2023 recorded 30 cases. Of that number, most of them happened to children. Therefore, we as students of Teaching Campus 6 conducted an activity that aims to foster mutual awareness regarding the prevention of sexual abuse in children. The methods used in this activity are discussion and seminar methods. The results of this seminar activity are increased awareness, concern and insight of students related to sexual harassment, as well as how to prevent and handle victims of sexual harassment both at school and in the community.